Split intein-mediated protein trans-splicing to express large dystrophins - Tasfaout, Hichem; Halbert, Christine L.; McMillen, Timothy S.; Allen, James M.; Reyes, Theodore R.; Flint, Galina V.; Grimm, Dirk; Hauschka, Stephen D.; Regnier, Michael; Chamberlain, Jeffrey S. (Nature, 2024)
Gene replacement using adeno-associated virus (AAV) vectors is a promising therapeutic approach for many diseases1,2. However, this therapeutic modality is challenged by the packaging capacity of AAVs (approximately 4.7 kilobases)3, limiting its application for disorders involving large coding sequences, such as Duchenne muscular dystrophy, with a 14 kilobase messenger RNA. Here we developed a new method for expressing large dystrophins by utilizing the protein trans-splicing mechanism mediated by split inteins. We identified several split intein pairs that efficiently join two or three fragments to generate a large midi-dystrophin or the full-length protein. We show that delivery of two or three AAVs into dystrophic mice results in robust expression of large dystrophins and significant physiological improvements compared with micro-dystrophins. Moreover, using the potent myotropic AAVMYO4, we demonstrate that low total doses (2 × 1013 viral genomes per kg) are sufficient to express large dystrophins in striated muscles body-wide with significant physiological corrections in dystrophic mice. Our data show a clear functional superiority of large dystrophins over micro-dystrophins that are being tested in clinical trials. This method could benefit many patients with Duchenne or Becker muscular dystrophy, regardless of genotype, and could be adapted to numerous other disorders caused by mutations in large genes that exceed the AAV capacity.